Power Meter Monitoring Dengan Mobile Apps dan Metode Direct Calculation - Kevin Wibisono Lokananto; Resmana Lim; Alexander Setiawan (Jurnal Infra, 2020)
Electricity is a basic need that is still not optimal in Indonesia, and the waste of electricity in Indonesia which is quite large, therefore with this tool can help to save electrical energy, but it can also monitor the burden attached to the tool can help manage financial because this tool displays total usage and total price.The tool that I made consisted of several main components such as the Arduino microcontroller, the ZMPT101B voltage sensor module, the ACS712 30A current sensor module. From the installed load, the data in the form of voltage and current will be read by the sensor and sent to the microcontroller for calculation.The calculation results will be uploaded to Firebase, which later will be fetched and showed by the Android application, The application will also be equipped with other features such as, on-off switch, reset, history,setkwh and total cost .